2019
DOI: 10.1155/2019/6941907
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Triangular Deployment of Underwater Wireless Acoustic Sensor Network considering the Underwater Environment

Abstract: In this paper, we propose an adaptive triangular deployment algorithm that can adjust sensor distribution depending on the variation in communication performance in an underwater environment. To predict the distance between sensor nodes, a performance surface model is implemented by estimating the communication performance based on spatio-temporal environment factors affecting the communication performance of the underwater sensor node. Subsequently, the performance surface model is applied to the adaptive tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…The technique assesses ideal holding time and also utilizes various routing parameters such as localization‐free signal‐to‐noise ratio (LSNR), signal quality index (SQI), and energy cost function (ECF), to tackle flooding, path loss, and broadcast dormancy. Kim et al 10 suggested an adaptive triangular deployment procedure regulating node dissemination depends on the disparity in transmission activities in an underwater atmosphere.…”
Section: Related Workmentioning
confidence: 99%
“…The technique assesses ideal holding time and also utilizes various routing parameters such as localization‐free signal‐to‐noise ratio (LSNR), signal quality index (SQI), and energy cost function (ECF), to tackle flooding, path loss, and broadcast dormancy. Kim et al 10 suggested an adaptive triangular deployment procedure regulating node dissemination depends on the disparity in transmission activities in an underwater atmosphere.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, the VODA increases the network coverage percentage than the other deployment scheme. Woojoong Kim et al 20 developed an adaptive triangular deployment of UASN in underwater environment. Based on the performance of surface model, the distances between the nodes were predicted.…”
Section: Related Workmentioning
confidence: 99%
“…Most terrestrial WSNs adopt two-dimensional (2D) sensor deployment models, and little attention has been paid to threedimensional (3D) sensor deployment models. In recent years, there has been an increase in the WSN application in 3D real-world scenarios due to the development of related technologies and the urgent demands of various industries, such as military monitoring, industrial area monitoring, air pollution monitoring, alpine and underwater monitoring, and emergency response and disaster relief [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%